Treatment of Brachial Plexus Injuries following Gunshot Injuries: A Systematic Review - Rohun Gupta; Isabel Herzog; Lauren Phung; Jacquelyn Roth; Joseph Weisberger; Margaret Luthringer; Edward S. Lee; Ashley Ignatiuk (Advances in Orthopedics)
Introduction. Brachial plexus injuries (BPI) from gunshot injuries are uncommon but usually severe and can cause chronic pain, loss of function, and permanent nerve damage. Multiple surgical techniques including neurolysis, end-to-end suture repair, and graft repair have been described for the treatment of these injuries. However, surgical indication, timing, and technique for these injuries remain controversial. This systematic review aims to investigate the treatment modalities for patients with BPI due to gunshot-related injuries. Methods. The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) methodology was employed for this review. PubMed, Cochrane Reviews, Embase, and CINAHL databases were included. The following keywords constituted our search criteria: gun-shot-wounds, brachial plexus, traum∗, and management. Results. A total of 90 studies were imported for screening, from which 9 papers met our final inclusion/exclusion criteria. The most common studies utilized in this review were retrospective chart reviews followed by case series. In total, there were 628 patients that suffered from gunshot wounds to the brachial plexus. Most patients underwent some form of delayed nerve repair consisting of neurolysis, end-to-end epineural repair, or graft repair with a sural or antebrachial cutaneous nerve graft. Several patients suffered from complications, with neuroma being the most common long-term complication that required reoperation. Conclusion. The optimal timing for surgeries involving BPIs should be determined after examining the level of nerve damage, associated injuries, operative risks, and electrophysiological workup for indications of spontaneous regeneration. Early surgical interventions were indicated for patients presenting with associated vascular or thoracic injuries, compressive masses, and nerve transection by sharp instruments in most selected papers.